Vibroacoustic response of steel–timber composite elements. (15th November 2022) - Chocholaty, B.; Roozen, N.B.; Maeder, M.; Marburg, S.
Abstract: With the increasing demand for sustainable construction and, at the same time, for larger spans in buildings and high-rise buildings, composite timber structures are gaining more attention, and steel–timber hybrid elements offer a promising approach. Therefore, this study analyzes a novel steel–timber composite floor structure experimentally and numerically. The investigations focus on the vibrational behavior of the structures while considering nonlinearities due to frictional effects in joints. First, eigenfrequencies, damping properties, and consequently, the vibrational characteristics of the systems are determined. Then, detection of nonlinearity follows, investigating amplitude-dependent stiffness and damping and the occurrence of higher harmonics. Results reveal nonlinearities indicated by the occurrence of higher-order harmonics and slight amplitude-dependent damping. Furthermore, the influence of parameters, such as steel thickness and fastener type, on the vibrational behavior of the structures is investigated, comparing specimens of various configurations. Finally, the experimental results validate a linear Finite Element model using the commercial software ANSYS as a first approach despite the nonlinearities that occurred during the measurements. Nonetheless, further investigations could deal with nonlinear models to get more detailed insight. Highlights: Steel–timber structures are investigated in vibroacoustic terms. Experimental and numerical methods are used. Nonlinear effects in the joints are considered. Low amplitude dependence and higher harmonic were detected.